Context‐dependent costs and benefits of tuberculosis resistance traits in a wild mammalian host. Issue 24 (6th December 2018) - Tavalire, Hannah F.; Beechler, Brianna R.; Buss, Peter E.; Gorsich, Erin E.; Hoal, Eileen G.; le Roex, Nikki; Spaan, Johannie M.; Spaan, Robert S.; van Helden, Paul D.; Ezenwa, Vanessa O.; Jolles, Anna E.
Abstract: Disease acts as a powerful driver of evolution in natural host populations, yet individuals in a population often vary in their susceptibility to infection. Energetic trade‐offs between immune and reproductive investment lead to the evolution of distinct life history strategies, driven by the relative fitness costs and benefits of resisting infection. However, examples quantifying the cost of resistance outside of the laboratory are rare. Here, we observe two distinct forms of resistance to bovine tuberculosis (bTB), an important zoonotic pathogen, in a free‐ranging African buffalo ( Syncerus caffer ) population. We characterize these phenotypes as "infection resistance, " in which hosts delay or prevent infection, and "proliferation resistance, " in which the host limits the spread of lesions caused by the pathogen after infection has occurred. We found weak evidence that infection resistance to bTB may be heritable in this buffalo population ( h 2 = 0.10) and comes at the cost of reduced body condition and marginally reduced survival once infected, but also associates with an overall higher reproductive rate. Infection‐resistant animals thus appear to follow a "fast" pace‐of‐life syndrome, in that they reproduce more quickly but die upon infection. In contrast, proliferation resistance had no apparent costs and was associated with measures of positive host health—such as having a higher body condition and reproductive rate. This study quantifies striking phenotypic variation in pathogen resistance and provides evidence for a link between life history variation and a disease resistance trait in a wild mammalian host population. Abstract : Here, we identify two distinct forms of tuberculosis resistance that come at distinct fitness costs in a wild population of African buffalo. This empirical evidence directly supports previous theoretical work in evolutionary trade‐offs and provides a novel example of differences in pace‐of‐life life history evolution in a wild mammal. Furthermore, we present a novel method for the estimation of heritability using marker‐based relatedness estimates.